2021
DOI: 10.3389/fnhum.2021.679086
|View full text |Cite
|
Sign up to set email alerts
|

Symphony of Well-Being: Harmony Between Neural Variability and Self-Construal

Abstract: Both neural activities and psychological processes vary over time. Individuals with interdependent self-construal tend to define themselves and adjust their behaviors to social contexts and others. The current research tested the hypothesis that the coordination between interdependent self-construal and neural variability could predict life satisfaction changes in university freshmen. We integrated resting-state functional magnetic resonance imaging scanning and self-construal assessment to estimate self-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Neural variability, which refers to the temporal variability in regional functional connectivity, may be an indicator of brain flexibility and adaptability or a predictor of neural rehabilitation [51] . Recent studies on neural variability have also shown its predictive effect on life satisfaction and recovery from depressive symptoms [16] , [17] . Moreover, research has shown that the across-trial variability in the neural response is significantly correlated with trial history-dependent response time changes and that neural variability in the premotor cortex can predict motor task performance [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Neural variability, which refers to the temporal variability in regional functional connectivity, may be an indicator of brain flexibility and adaptability or a predictor of neural rehabilitation [51] . Recent studies on neural variability have also shown its predictive effect on life satisfaction and recovery from depressive symptoms [16] , [17] . Moreover, research has shown that the across-trial variability in the neural response is significantly correlated with trial history-dependent response time changes and that neural variability in the premotor cortex can predict motor task performance [33] .…”
Section: Introductionmentioning
confidence: 99%
“…People with higher positive affect had more diversity in the connections of the insula with other brain regions. Similarly, Fan et al (2021) reported that the whole brain self-dependent neural variability (i.e., the variability of functional connectivity between all regions across the brain) is associated to higher satisfaction with life. fNRIS…”
Section: Resultsmentioning
confidence: 94%